Biochar production through hydrothermal carbonization of sewage sludge a plant design - Abaya, Rodgee F.; Matuba, Jan Samuel C.; Sanglay, John Paul Nino A. (College of Engineering, University of the Philippines Diliman, 2016)
The recent and on-going rehabilitation and establishment of sewage treatment plants (STP) in Metro Manila will pose problems due to the increasing amount of produced byproduct of sewage sludge. Current practices for utilization and disposal of sewage sludge include landfilling and composting for agricultural applications which do not address the hazards posed by pathogens and toxic components. Incineration of sewage sludge reduces these hazards but is energy-intensive due to the required pre-treatment processes. These methods are not sustainable for long-term applications. With hydrothermal carbonization (HTC), energy from sewage sludge can be recovered by conversion into biochar which can be used as an alternative solid fuel with comparable properties with that of bituminous coal. An economic and technical feasibility study is conducted to assess the market opportunities of biochar as a clean bituminous coal substitute. The countrys increasing demand for energy causes the increase in demand for coal, Since bituminous coal is a major contributor in the Philippine coal industry, this is a great opportunity to introduce the product to compete in the local market especially with the global trend to switch into renewable energy sources. The main limitation for the production of biochar, however, is posed by the sewage sludge production rates of the STPs. But with the continuous development of the wastewater treatment industry, continuously increasing supply of the raw material is guaranteed. From the preliminary feasibility study, the plant site will be located at Paco, Manila with raw material sourced from STPs in Quezon City. Further assessment of the site includes evaluation of disaster risk, community peace and order, and tax and wage rates. The preliminary studies done for the design project established the market for biochar as a potential substitute for bituminous coal. While it is the main target of market entry, biochar can also be marketed as a co-firing material for different types of coal. This is practice already being done in countries promoting renewable source of energy. The biochars price is set to match the forecasted price of bituminous coal in order to directly compete with it. The proposed HTC plant reaction is designed to operate at 140°C and 2 MPa to process an annual feed capacity (full) of 17,100 tons of sewage sludge, which are provided by selected Maynilad STPs to produce 1,200 tons of biochar. The operation is set at 50 percent capacity in 2028, 75 percent in 2029, to 100 percent in 2030 and succeeding years. The design of the hydrothermal carbonization process required general safety and environmental consideration because of the presence of toxic compounds. The environmental concerns are addressed by establishing a treatment unit in order to satisfy effluent standard requirements. Inherent safety design is done for the materials handling, processing, and control. Safety and los hazards, control of the process, and limitation of losses. Further evaluation is performed by conducting relief scenario analysis and hazards and operability study. One of the main focuses in the design process is the economic considerations in designing the major equipment and piping and instrumentation in the plant. A total of 5 units are designed namely: Raw Material and Product Storage, Hydrothermal Carbonization, Biochar Product Separation, Plant Water Treatment, and Compressed Air Treatment to generate a total of 18 P&IDs. Many technical issues have been addressed in the detailed equipment sizing and design and line sizing. Lastly, the plant layout is designed accordingly under the general considerations in separation and elevation levels in order to address safety issues